2009
DOI: 10.21608/mjae.2009.109500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alternate-Long Furrows Irrigation on Calcareous Soils Productivity

Abstract: Field experiment was conducted along two successive seasons of winter (2004/2005) and summer (2005) at Maryout Experimental Station of the Desert Research Center, to evaluate the performance of alternate-long furrow irrigation system, using three irrigation water inflow rates on faba bean and sunflower crops productivity grown in calcareous soil. The experiments carried out in a split plot design with four replicates at random procedure. Irrigation system treatments were used as the main plots (120 m length wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…Average Wa values over the two growing seasons were presented in Table (2 Considering irrigation intervals, lowest seasonal amount of water applied (Wa) with AFI treatments as compared to EFI might be due to the great reduction of wetted surface in AFI; almost half of the soil surface is wetted in AFI as compared to EFI. This result supports the outcome obtained by Hiekal et al (2009), who found that AFI methods can supply water in a way that greatly reduces the amount of wetted surface, which leads to less evapotranspiration and less deep percolation. The amount of (Wa) with surge alternative techniques were less than EFI and AFI.…”
Section: Seasonal Amount Of Water Applied (Wa)supporting
confidence: 91%
“…Average Wa values over the two growing seasons were presented in Table (2 Considering irrigation intervals, lowest seasonal amount of water applied (Wa) with AFI treatments as compared to EFI might be due to the great reduction of wetted surface in AFI; almost half of the soil surface is wetted in AFI as compared to EFI. This result supports the outcome obtained by Hiekal et al (2009), who found that AFI methods can supply water in a way that greatly reduces the amount of wetted surface, which leads to less evapotranspiration and less deep percolation. The amount of (Wa) with surge alternative techniques were less than EFI and AFI.…”
Section: Seasonal Amount Of Water Applied (Wa)supporting
confidence: 91%